IMPLEMENTASI MANAJEMEN BERBASIS SEKOLAH (MBS) DAN PENGELOLAAN DANA BANTUAN OPERASIONAL SEKOLAH (BOS) SEKOLAH DASAR NEGERI DI WILAYAH KECAMATAN RATOLINDO KABUPATEN TOJO UNA-UNA - Mohamad, Selfi (Katalogis, 2017)
The purpose of this study are: 1) to explore and analyze the implementation of school-based management and 2) to explore and analyze the management of school operational support grants in elementary schools in the area of Ratolindo Sub-District, Tojo Una-Una. The study applies descriptive methods with quantitative and qualitative approaches. Sample includes 33 respondents from 3 schools (SDN 8, SDN 3, and SDN 12) as the largest beneficiaries of BOS grant that is pusposively selected. Respondents are the principals, treasurer who handles BOS grants in The Department of Education, Youth, and Sport, teacher representatives, school committees, and student parents. The result shows that the implementation of school-based management in elementary schools in the area of Ratolindo Sub-District, Tojo Una-Una is rated â€˜goodâ€™ with a mean of 4.48. Indicator with the higest mean is solid teamwork with independency and accountability in managing the school operational support grants. The â€˜weakâ€™ indicator relates with participation in decision making. Also, participation level of parents, especially in celebration of national holidays that are not covered by BOS grants. Overall the management of BOS grants is rated â€˜goodâ€™ with mean of 4.69. Indicator with the highest mean in the preparation of school-budget plan, budget verification, and transaprancy and accountability in managing the grant. However, there is a school, SDN 12, which does not open access for parents to report transparency-related matters. Furthermore, SDN 8 has not posted information of Â â€œfree of cost education or this school is secured by BOS fundsâ€.